Recurrence of testicular cancer – only VeIP? - Świątoniowski, Grzegorz; Brużewicz, Szymon (Contemporary Oncology/Współczesna Onkologia, 2008)
The recurrence of germ cell tumours (GCT) after radical treatment still gives the possibility of successful treatment. There are some objective difficulties in the optimization of therapy, however, which are mostly related to the deficiency of highly reliable clinical data. Studies carried out in the 1980s revealed that ifosfamide- or cisplatin-based therapeutic protocols are efficient in the cases discussed. Their application may result in slightly more than 20% of recoveries. Many hopes are place on attempts with so-called “new drugs” – particularly paclitaxel and gemcitabine – used together with cisplatin in second line treatment. There are some reports which suggest the predominance of such programmes over the classical ifosfamide- and cisplatin-based therapies. An alternative approach is the application of high-dose chemotherapy (HDCT) with subsequent bone marrow or – currently more frequent – stem cell transplantation. Markedly over-treated patients (second recurrence) were qualified to early phase I/II trials, however, which was reflected in their results (low efficiency and poor tolerance of HDCT). The results became more promising when more restricted qualification criteria were used (only patients with first recurrence, exclusion of subjects with primary mediastinal location) and the transplantation techniques improved. Unfortunately, a phase III trial (IT 94) did not prove the advantages of HDCT over non-myeloablative treatment of recurrent GCT. There is some new evidence, however, according to which HDCT is advisable in certain groups of patients.